Speciálněpedagogická diagnostika a intervence u žáků se specifickými poruchami učení Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Bartoňová, Miroslava (Masaryk University Press, 2019)
Title in English: Special Educational Diagnostics and intervention in Pupils with SLD: Methodical texts for the MUNI 4.0 project. Intervention and correction of specific learning disorders is demanding, long-term, and requires considerable effort from the pupil, teacher, family, and other professionals. The development of specific learning disorders is understood as a process that can be experienced in several stages. Intervention techniques are various procedures that affect the development of reading skills. They help pupils to think over the text and lead them to real understanding and reading experience. This paper provides basic information on specific learning disorders in relation to intervention and simulation. Its goal is to help intended teachers adopt strategies to help them master the learning process.